Inoculação de sementes de milho com Azospirillum brasilense associada à fertilização com cama de frango - Vitto, Deise Cadorin (2019)
Maize is one of the most economically important crops for Brazil. Which is why, the search for suitable forms for plant nutrition, such as organic fertilizers combined with the use of microorganisms that promote plant growth is of great importance in achieving cost reduction, balance, and sustainability in modern agriculture. For that matter, the aim of this paper was to study the effect that the inoculation of seeds with A. brasilense combined with poultry manure fertilization would have on maize plants. The experiment was conducted in two areas arranged in a 2 x 6 factorial randomized block design. The first factor consisted of the maize inoculation with A. brasilense and the control group; the second factor was, six poultry manure doses pre-established by the fertilization recommendation analysis, using 0, 50, 100, 150, 200, 250% of the recommended dose for each area. Morphometric analysis (plant height and basal stem diameter), destructive analysis (total dry matter mass, dry matter mass of leaf and stem plus sheath, and leaf area), and SPAD index in the plants were performed 60 days after sowing (DAS). At 90 DAS gas exchange measurements, such as the net CO2 assimilation rate of plants (A), stomatal conductance (gs), leaf transpiration (E), and water use efficiency (WUE) were evaluated. Nitrogen, phosphorus, and potassium levels were analyzed 100 DAS. At 150 DAS, production and productivity components were determined. When compared to the control sample (without seed inoculation), the A. brasilense fostered the increase of leaf dry matter positively influencing productivity and the foliar content of phosphorus on the 1000-grain weight. Seed inoculation with A. brasilense affected the assimilation rate of CO2 in maize plants. The poultry manure had a positive influence on leaf phosphorus and potassium levels showing that the ideal dose of poultry manure to reach the maximum phosphorus content in the leaf was 5830 kg ha-1. Fertilization with poultry manure promoted height increments, basal diameter of the stem, dry mass of the plants and maize yield. To reach the maximum dry mass production of the aerial part the recommended dose of poultry manure was 6267 kg ha-1.